1982
DOI: 10.1135/cccc19821444
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of strontium and barium by nitrobenzene solution of dicarbolide in the presence of polyethylene glycols

Abstract: Extraction of microamounts of Sr2+ and Ba2+ from 0.2-1.0M-HClO4 by the nitrobenzene solutions of dicarbolide H+[Co(C2B9H11)2]- in the presence of polyethylene glycols (PEG) (Mr = 200, 300, 400) has been investigated. It has been found that the extraction of the protonized polyethylene glycol molecule (H+ + L ##e HL+, where the bar denotes species present in the organic phase) and the extraction of the complex between the extracted ion and polyethylene glycol, i.e., M2+ +L + 2 H+ ##e ML2+ + 2 H+, are the predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(18 citation statements)
references
References 0 publications
4
14
0
Order By: Relevance
“…A subroutine UBBE, based on the relations given above, the mass balance of the N,N,N',N'-tetrabutyl-1,10phenanthroline-2,9-dicarboxamide (L) ligand and the electroneutrality conditions in both phases of the system under consideration, was formulated 36,37 and introduced into a more general least-squares minimizing program LETAGROP 38 used for determination of the "best" values of the extraction constants K ex (ML The values log K D = 2.2 (see Table 5, footnote a), logβ(HL + org ) = 9.4 ( Tables 3 and 4. From these tables it is evident that the extraction data can be best explained assuming the complexes ML a The values of the extraction constants are given for each complex.…”
Section: Resultsmentioning
confidence: 99%
“…A subroutine UBBE, based on the relations given above, the mass balance of the N,N,N',N'-tetrabutyl-1,10phenanthroline-2,9-dicarboxamide (L) ligand and the electroneutrality conditions in both phases of the system under consideration, was formulated 36,37 and introduced into a more general least-squares minimizing program LETAGROP 38 used for determination of the "best" values of the extraction constants K ex (ML The values log K D = 2.2 (see Table 5, footnote a), logβ(HL + org ) = 9.4 ( Tables 3 and 4. From these tables it is evident that the extraction data can be best explained assuming the complexes ML a The values of the extraction constants are given for each complex.…”
Section: Resultsmentioning
confidence: 99%
“…DCC in H-form is known to be a superacid and dissociates completely in polar organic solvents [2]. The authors [4] showed that during the extraction process the hydrated proton of H-DCC acid in organic phase (H § O, n = 5,5) is exchanged to the strongly hydrated strontium cation, Sr(H20)2+n, (n = 12,1-12,3). Addition of PEG into this system results in the displacement of a portion of water molecules from the hydrate shells of the proton and strontium, to form the cation complexes of the composition H+.(PEG-400).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the distribution coefficient of Sr 2+ increases by a factor of 103 in the presence of PEG. According to [4], each oxyethyl group of PEG is capable of displacing one water molecule from hydrate shell of the strontium cation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations